Investigation on the electrical properties of palm oil under different concentration of recycle organic material (pepper seed) doping in transformer application - Muhamad Faiz Md Dina,; Mohd Faiz Zakaria,; Nazrul Fariq Makmor,; Wan Fathul Hakim Wan Zamri,; Wang, Jianli; Dou, Shi Xue (Penerbit Universiti Kebangsaan Malaysia, 2021)
Many researchers nowadays are looking to find another alternative to replace the use of mineral oil as an insulation fluid used in transformer due to the amount of minerals oil that are depleted. One of the alternatives is by using palm oil as an insulation fluid. However, something must be done to improve the breakdown voltage of palm oil if it wants to replace the use of mineral oil as an insulation fluid. One of approved methods to improve the dielectric strength of palm oil is by inserting another particle inside the oil. In this study, an investigation will be carried out to observe the effect of recycling organic material (black pepper) doping on Refined Bleached Deodorized Palm Oil (RBDPO) for AC breakdown voltage application will be carried out. It is concluded that, 2.5 mm gap between two electrodes produce the highest breakdown voltage compared with 1.5 mm and 2.0 mm. Other than that, the smallest size of black pepper which is 150 mm shows having the highest breakdown voltage compared to 300 mm and 600 mm. A test with different concentration of pepper seed with 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.4%, and 0.5% were conducted and shows that the breakdown voltage starts to increase as the concentration increases from 0.01% until 0.15% and start decreasing from 0.02% until 0.5%. Black pepper doping inside the palm oil does increase the performance of palm oil up to 13% from 49.66 kV to 57.4 kV.